Effects of the Diabetic Condition on Grafted Fat Survival: An Experimental Study Using Streptozotocin-Induced Diabetic Rats - Jung, Jae A; Kim, Yang Woo; Cheon, Young Woo; Kang, So Ra (Archives of plastic surgery, 2014)
Background Autologous fat grafts have been widely used for cosmetic purposes and for soft tissue contour reconstruction. Because diabetes mellitus is one of the major chronic diseases in nearly every country, the requirement for fat grafts in diabetes patients is expected to increase continuously. However, the circulation complications of diabetes are serious and have been shown to involve microvascular problems, impairing ischemia-driven neovascularization in particular. After injection, revascularization is vital to the survival of the grafted fat. In this study, the authors attempted to determine whether the diabetic condition inhibits the survival of injected fat due to impaired neovascularization. Methods The rat scalp was used for testing fat graft survival. Forty-four seven-week-old male Sprague-Dawley rats were allocated to a diabetic group or a control group. 1.0 mL of processed fat was injected subcutaneously into the scalp of each rat. The effect of diabetes was evaluated by calculating the volume and the weight of the grafted fat and by histologically analyzing the fat sections. Results The surviving fat graft volume and weight were considerably smaller in the diabetic group than in the control group (P<0.05), and histological evaluations showed less vascularity, and more cysts, vacuoles, and fibrosis in the diabetic group (P<0.05). Cellular integrity and inflammation were not considerably different in the two groups. Conclusions As the final outcome, we found that the presence of diabetes might impair the survival and the quality of fat grafts, as evidenced by lower fat graft weights and volumes and poor histologic graft quality.